Pegasus descending : a Dave Robicheaux novel - Burke, James Lee (Simon & Schuster, 2006)
Detective Dave Robicheaux is facing the most painful and dangerous case of his career. A troubled young woman breezes into his hometown of New Iberia, Louisiana. She happens to be the daughter of Robicheaux's onetime best friend--a friend he witnessed gunned down in a bank robbery, a tragedy that forever changed Robicheaux's life. The twists begin when Trish Klein--the only offspring of Robicheaux's Vietnam-era buddy--starts passing marked hundred-dollar bills in local casinos. Is she a good kid gone bad? A victim's child seeking revenge? A promiscuous beauty seducing everyone good within her grasp? And how does her behavior relate to the apparent suicide of another "good" girl, an ace student named Yvonne Darbonne, who apparently participated in a college frat orgy before her death?--From publisher description.